Sex-Dependent Changes in miRNA Expression in the Bed Nucleus of the Stria Terminalis Following Stress - Mavrikaki, Maria; Pantano, Lorena; Potter, David; Rogers-Grazado, Maximilian A.; Anastasiadou, Eleni; Slack, Frank J.; Amr, Sami S.; Ressler, Kerry J.; Daskalakis, Nikolaos P.; Chartoff, Elena (Frontiers in Molecular Neuroscience, 2019)
Anxiety disorders disproportionately affect women compared to men, which may arise from sex differences in stress responses. MiRNAs are small non-coding RNAs known to regulate gene expression through actions on mRNAs. MiRNAs are regulated, in part, by factors such as stress and gonadal sex, and they have been implicated in the pathophysiology of multiple psychiatric disorders. Here, we assessed putative sex differences in miRNA expression in the bed nucleus of the stria terminalis (BNST)—a sexually dimorphic brain region implicated in anxiety—of adult male and female rats that had been exposed to social isolation (SI) stress throughout adolescence. To assess the translational utility of our results, we assessed if childhood trauma in humans resulted in changes in blood miRNA expression that are similar to those observed in rats. Male and female Sprague-Dawley rats underwent SI during adolescence or remained group housed (GH) and were tested for anxiety-like behavior in the elevated plus maze as adults. Small RNA sequencing was performed on tissue extracted from the BNST. Furthermore, we re-analyzed an already available small RNA sequencing data set from the Grady Trauma Project (GTP) from men and women to identify circulating miRNAs that are associated with childhood trauma exposure. Our results indicated that there were greater anxiogenic-like effects and changes in BNST miRNA expression in SI versus GH females compared to SI versus GH males. In addition, we found 9 miRNAs that were regulated in both the BNST from SI compared to GH rats and in blood samples from humans exposed to childhood trauma. These studies emphasize the utility of rodent models in studying neurobiological mechanisms underlying psychiatric disorders and suggest that rodent models could be used to identify novel sex-specific pharmacotherapies for anxiety disorders.